Acute effect of cigarette smoking on frontal planar QRS-T angle in apparently healthy subjects with habitual smoking - Ozdemir, Levent (Journal of Surgery and Medicine, 2020)
Aim: It has been well recognized that smoking exerts various detrimental cardiovascular effects. Although the effect of chronic smoking on cardiac electrophysiology is well known, little is known about the effect of acute smoking on surface ECG. Previous reports suggested that frontal planar QRS-T angle (fpQRS-Ta), measured by surface ECG, may be associated with ventricular arrhythmias and cardiac death. Hence, we primarily aimed to assess the effect of acute smoking on fpQRS-Ta. Methods: A total of 92 apparently healthy subjects [44 female, 48 male, mean age 38.7(8.02) years] with smoking habit were enrolled in this prospective cohort study between May-July 2019. Demographic and clinical characteristics were recorded, and fpQRS-Ta together with some ECG parameters were noted before and 10 minutes after smoking for comparison. Spearman’s analysis was implemented to seek the probable correlation of the difference between pre- and post-smoking ECG parameters. Results: Ten minutes after smoking, median heart rate, QRS duration and fpQRS-Ta increased significantly (72.6 beats/min vs 81.5 beats/min, P<0.001; 84 ms vs 86 ms, P=0.012; 14.5° vs 25°, P<0.001; respectively), while PR and QTc duration did not significantly change (150.0 ms vs 150.0 ms, P=0.774; and, 423.5 ms vs 429.5 ms, P=0.372). In Spearman’s correlation analysis, the difference between pre- and post-smoking fpQRS-Ta significantly and negatively correlated with C-reactive protein (CRP) levels (r: -0.272, P=0.027). Conclusion: Acute smoking may widen fpQRS-Ta in healthy habitual smokers, and serum CRP negatively correlates with the degree of fpQRS-Ta widening. Our observation may further enlighten the pathophysiological mechanism of smoking in cardiac arrhythmias and sudden death.